The use of in vitro methods in assessing human health risks associated with short‐chain perfluoroalkyl and polyfluoroalkyl substances (PFAS). Issue 8 (6th December 2021) - Solan, Megan E.; Lavado, Ramon
Abstract: Perfluoroalkyl and polyfluoroalkyl substances (PFAS) are a large class of industrial chemicals with a ubiquitous and persistent presence in the environment. Of the thousands of PFAS used by consumers and industry, very few have been thoroughly characterized for potential adverse effects. This is especially true for the novel short‐chain (C < 8) alternatives that replaced legacy PFAS. Perfluoroalkyl and polyfluoroalkyl substances have revealed inconsistencies in the toxicokinetics predicted by animal models and empirical findings in humans. To adequately assess the possible health effects of short‐chain PFAS, there is a need for robust aggregated data sets on the mechanistic underpinnings and physiochemical properties of these alternatives. Acquiring relevant data on the health effects of short‐chain PFAS can be achieved through high‐throughput methods supported by in vitro human cell‐based models. This review briefly summarizes some of the toxicity data obtained using human cells in vitro, discusses the advantages and limitations of cell‐based models, and provides insights on potential solutions to challenges presented with the use of these methods for use in safety assessments. Abstract : Studies evaluating short‐chain perfluoroalkyl and polyfluoroalkyl substances (PFAS) have revealed inconsistencies in the toxicokinetics predicted by animal models and empirical findings in humans. Acquiring relevant data on the health effects of short‐chain PFAS in humans can be achieved through high‐throughput methods supported by human cell‐based models. This review summarizes some of the short‐chain PFAS toxicity data obtained using human cells in vitro, discusses their advantages and limitations, and offers potential solutions for implementation in safety assessments.